An expert-approved R&D model - Zeeshan, Asim; Tan*, Seng Teck; Shahryar, Sorooshian (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The initial intention of this descriptive analysis is to confine closer encounter regarding the potential impact of supporting management discipline on R&D in public organization among developing countries. In this, context prior theories on R&D in Public organizations draw some conceptual models with limited narratives on how to manage supporting management discipline. Some prior studies draw capabilities prospective related to knowledge, innovation and technology management as supporting management discipline that shares their boundaries with R&D under individual context. Based on their relationship this study developed a conceptual framework to draw significance of supporting management discipline on R&D that has been long been striving to convene capability prospective among developing countries. The author analysis based on R&D fit to the context of public organization and portrays case of Pakistan under Focus Group Discussion. The experts from 81 R&D of public organizations were involved; where 195 participants are, compose into 41 Focus Groups. The outcome of Focus Group Discussion shows that process, infrastructure and strategic are consider as potential criteria’s that draw relationship among capabilities related knowledge, innovation and technology management disciplines.